SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-4032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuel Properties on Spray Development from a Multi-Hole DISI Engine Injector

Abstract: Extensive literature exists on spray development, mixing and combustion regarding engine modeling and diagnostics using single-component and model fuels. However, often the variation in data between different fuels, particularly relating to spray development and its effect on combustion, is neglected or overlooked. By injecting into a quiescent chamber, this work quantifies the differences in spray development from a multi-hole direct-injection spark-ignition engine injector for two single-component fuels (iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 10 publications
6
66
0
Order By: Relevance
“…It should be also be mentioned here for completeness that high-volatility components like n-pentane have been found to be suitable single components to mimic gasoline's spray behaviour at relevant conditions (e.g. see van Romunde et al, 2007;van Romunde and Aleiferis, 2009). Additionally ethanol has shown similar behaviour to gasoline in terms of spray effects related to temperature and pressure conditions (e.g.…”
Section: Vapour Typesmentioning
confidence: 90%
See 1 more Smart Citation
“…It should be also be mentioned here for completeness that high-volatility components like n-pentane have been found to be suitable single components to mimic gasoline's spray behaviour at relevant conditions (e.g. see van Romunde et al, 2007;van Romunde and Aleiferis, 2009). Additionally ethanol has shown similar behaviour to gasoline in terms of spray effects related to temperature and pressure conditions (e.g.…”
Section: Vapour Typesmentioning
confidence: 90%
“…Figure 3 shows the distillation curve of a typical pump-grade gasoline, as well as the boiling points of some single components which are found in high concentration in gasoline, and thus the focus of the present study (more details about the curves can be found in van Romunde et al, 2007;van Romude and Aleiferis, 2009;Aleiferis et al, 2010a-b;Serras-Pereira et al, 2012. In particular, some of the vapour properties of n-pentane, ethanol, iso-octane, toluene, o-xylene and benzene are presented in Table 2 at 298 K and 315 K (Yaws, 2003); density values are also shown from ideal gas calculations.…”
Section: Vapour Typesmentioning
confidence: 99%
“…The investigation used the same injection system and facilities described in previous publications by the authors [22][23][24][25][26][27]. Therefore primarily deviations from standard equipment, i.e.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…This was achieved using a real-size optical nozzle to simulate the flow in one of 8 the holes of a real multi-hole injector previously used by the authors for macroscopic spray imaging and related engine studies [22][23][24][25][26][27]. These studies showed that the geometry and break-up of sprays from such injectors is significantly affected by operating conditions, which result in a high degree of superheating of the fuel components, i.e.…”
Section: Present Contributionmentioning
confidence: 99%
See 1 more Smart Citation